Design and analysis of randomized clinical trials requiring prolonged observation of each patient. II. analysis and examples. - Peto, R; Pike, M; Armitage, P; Breslow, N; Cox, DR; Howard, S; Mantel, N; McPherson, K; Peto, J; Smith, P (1977)
Part I of this report appeared in the previous issue (Br. J. Cancer (1976) 34,585), and discussed the design of randomized clinical trials. Part II now describes efficient methods of analysis of randomized clinical trials in which we wish to compare the duration of survival (or the time until some other untoward event first occurs) among different groups of patients. It is intended to enable physicians without statistical training either to analyse such data themselves using life tables, the logrank test and retrospective stratification, or, when such analyses are presented, to appreciate them more critically, but the discussion may also be of interest to statisticians who have not yet specialized in clinical trial analyses.